EXPLORATORY STUDY OF NANOPARTICLE SYNTHESIS USING PLANT EXTRACTS - Wijaya, Ronaldo
Nanoparticle developments are driven by its important role in pharmacy and medicine industry. Biological method, which is environmentally friendly and nontoxic, can be used as an alternative nanoparticle synthesis technique, such as ZnO. Tropical plants are used as biological agent because of their affordability. Antioxidant activity is remarked as a driving force to nanoparticle synthesis because of its reducing capability. Therefore, the researchers used eight plants, which are water spinach leaves, petai leaves, papaya leaves, avocado leaves, cashew leaves, papaya fruit, and starfruit. This research is undergone to verify tropical plant extracts that are feasible to obtain ZnO nanoparticles and analyze nanoparticle characteristics that have been produced. Those eight plants were extracted and mixed with Zn(NO3)2 precursor. Based on the Folin-Ciocalteu assay, there was no correlation between phenolic content and nanoparticle yield, while DPPH assay showed a proportional correlation between antioxidant activity and nanoparticle yield. ZnO nanoparticles were successfully synthesized from water spinach leaves, papaya fruit, avocado fruit, and starfruit. Phase characterization of calcinated nanoparticles resulting a peak at 31°-37° diffraction angle. Morphological characterization had shown nanoparticles shape changes after calcination, from spherical to oval and irregular. Considering particle sizes after calcination, sintering generally has larger effect than organic matter volatilization. DLS assay indicated that all nanoparticles were polydisperse and agglomerated in 706,2-936,1 nm range. Nanoparticles that were synthesized by papaya and avocado fruit are driven by C=C and S=O functional groups, while only C=C that has driven nanoparticles synthesis in water spinach leaves. The ZnS formation at nanoparticles outer layer had caused larger particle size in papaya and avocado fruit nanoparticles.